2011
DOI: 10.4065/mcp.2010.0309
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Obstructive Cardiomyopathy, Bleeding History, and Acquired von Willebrand Syndrome: Response to Septal Myectomy

Abstract: Bleeding with severe aortic stenosis is linked to acquired von Willebrand syndrome and loss of high-molecular-weight multimers of von Willebrand factor. Valve replacement resolves bleeding tendency and loss of high-molecular-weight multimers. We report outcomes in 5 patients with symptomatic obstructive hypertrophic cardiomyopathy and spontaneous gastrointestinal, mucosal, or excessive postsurgical bleeding in whom acquired von Willebrand syndrome was documented. All 5 patients underwent surgical septal myecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…We did not record serial observations of VWF activity indices over time, but the stability over a 24-hour period and directionally appropriate gradient reductions have been seen with treatment of hypertrophic cardiomyopathy (15,17) and with aortic valve replacement for AS (10,11). Small sample size prohibited a multivariate analysis of predictors of bleeding, but the 14% bleeding rate is similar to previously published estimates of 20% (10) and 17% (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not record serial observations of VWF activity indices over time, but the stability over a 24-hour period and directionally appropriate gradient reductions have been seen with treatment of hypertrophic cardiomyopathy (15,17) and with aortic valve replacement for AS (10,11). Small sample size prohibited a multivariate analysis of predictors of bleeding, but the 14% bleeding rate is similar to previously published estimates of 20% (10) and 17% (13).…”
Section: Discussionmentioning
confidence: 99%
“…The case for the use of a biomarker that reflects disease severity, reliably detects progression, and assesses prognosis and response to therapy was made in a recent comprehensive review of natriuretic peptides by Steadman and colleagues (9). In light of the strong graded relationship between functional abnormalities of von Willebrand factor (VWF) and AS gradient in surgical cases (10-14) and in hypertrophic cardiomyopathy with obstruction (15) and the correction of laboratory VWF functional abnormalities and clinical bleeding tendency with aortic valve replacement (AVR) (10,16) or septal myectomy in hypertrophic cardiomyopathy (17), we sought to assess the performance of VWF activity indices as biomarkers of AS severity across a broad range of disease, in patients who had undergone aortic valve replacement, and in comparison with brain natriuretic peptide (BNP).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently Blackshear et al 12 demonstrated the presence of an acquired von Willebrand deficiency in association with HCM and Schödel et al 13 demonstrated von Willebrand 2A deficiency presenting with epistaxis.
Learning points

Critical aortic stenosis is very common in the elderly.

Acquired von Willebrand syndrome: vWS-2A should be considered as a potential predisposing and perpetuating factor in gastrointestinal bleeding in people with severe aortic stenosis.

In light of the high prevalence of the condition clinical management of GI bleeding secondary to angiodysplasia or other sources should consider vWS-2A and its causes when structuring further investigation and treatments.

…”
Section: Discussionmentioning
confidence: 99%
“…The resulting acute severe pulmonary hypertension was the likely mechanism for the bland DAH, possibly further facilitated by acquired Von Willebrand disease in the setting of obstructive HCM. 3 Unfortunately, we did not evaluate our patient for loss of Von Willebrand factor.…”
Section: Discussionmentioning
confidence: 99%
“…A more common association is lower gastrointestinal bleeding resulting from acquired von Willebrand disease. 3 The key principle in the management of obstructive HCM is to implement lifestyle measures such as avoiding dehydration or excessive vasodilation (ie, alcohol, saunas, nitrates, phosphodiesterase-5 inhibitors, and certain antihypertensive drugs). Providers must also assess for the risk of sudden cardiac death and the role of implantable cardioverterdefibrillators for primary prevention.…”
Section: Dr Gersh (Cardiologist Hcm Specialist)mentioning
confidence: 99%